Novel Innovations for Ventricular Assist Device Infection. Issue 12 (10th August 2021) - Polycarpou, Andreas; Pahwa, Siddharth; Blackmon, Shanda H.; Stulak, John M.
Abstract : Device infection is a major potential complication following ventricular assist device implantation and can lead to devastating consequences. The treatment options are few and often challenging to implement. The most durable option may require device exchange to obtain adequate source control. Due to the prolonged support times offered by the new left ventricular assist devices (LVADs), there is concern that the number of patients that will eventually require repeated device exchanges for device infection will increase. The benefit of medical antibiotic therapy alone is limited and is frequently unsuccessful. Surgical treatment strategies that improve outcomes by eliminating the infection and by preventing infection recurrence are needed. We report a case of a third-time LVAD exchange (4th device implant) for device infection within eight years of the index implant, and we briefly discuss the role of the greater omentum in the surgical treatment of this complication.